2009
DOI: 10.1111/j.1600-0846.2009.00370.x
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of green tea extracts on photoaging and photommunosuppression

Abstract: Background: Health benefits of designed functional foods using dairy fermented products in co-production with medicinal herbs are under comprehensive investigations. Yoghurt has triggered a functional food revolution while green tea and Moringa oleifera represent precious source of high content of various types of antioxidants and micronutrients. Oxidative stress and lipid peroxidation are suggested mechanisms involved in lead toxicity. The aim of present study was to assess protective effects of green tea and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 35 publications
1
33
0
Order By: Relevance
“…20,21 Combinations of vitamins C, E, and polyphenolic extracts have been shown to have photoprotective effects in humans and pigs. [22][23][24][25] The second line of ''active'' protection with antioxidants can potentially boost the body's natural antioxidant reserve and quench free radicals generated from the residual UV rays that have bypassed the sunscreen filter and reach the skin.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Combinations of vitamins C, E, and polyphenolic extracts have been shown to have photoprotective effects in humans and pigs. [22][23][24][25] The second line of ''active'' protection with antioxidants can potentially boost the body's natural antioxidant reserve and quench free radicals generated from the residual UV rays that have bypassed the sunscreen filter and reach the skin.…”
Section: Discussionmentioning
confidence: 99%
“…[117,118]. Nichols and Katiyar [52] reported that green tea polyphenols, catechin, epigallocatechin, and epigallocatechin-3-gallate, function favorably as sunscreen supplements to protect the skin from the adverse effects of UV radiation-induced inflammation, oxidative stress, and DNA damage including the risk of developing skin cancers.…”
Section: Camellia Sinensis (Fam: Theaceae)mentioning
confidence: 97%
“…Polyphenols: catechin, epiglactocatechin, epiglactocatechin-3-gallate and so on Theaceae [164] Centella asiatica L. Urban. Increasing cellular hyperplasia; Collagen production; Granulation tissue levels of DNA, Protein, total collagen and hexosamine; Rapid maturation and cross-linking of collagen, etc Triterpenoids; Saponins including madecassoside, asiaticoside, centelloside, and asiatic acid Umbelliferae [97] Citrus sinensis L.…”
Section: Natural Sources Targeted Tissues and Mechanismsmentioning
confidence: 99%